Empirical Insights into the Symbiosis of Healthy Living and Physical Fitness among University Sports Students - Rahman, Dally (Performa, 2023)
A healthy lifestyle and physical fitness are two important variables to support the success of sports students in undergoing lectures. The purpose of this study was to determine the relationship between a healthy lifestyle and the physical fitness of students. The correlational research method was used in this study involving 32 male students. Healthy lifestyle data was collected using questionnaires while physical fitness data was obtained by conducting a cooper test, then the data was analyzed using the Pearson correlation formula. The results of this study showed a positive and significant relationship between a healthy lifestyle and students' physical fitness (r = 0.40, p = 0.00). The conclusion of this study is that the physical fitness of students is related to the healthy lifestyle of these students, with the regularity of their lifestyle and carried out in a disciplined manner, their fitness level will also be better